MYC Induces Oncogenic Stress through RNA Decay and Ribonucleotide Catabolism in Breast Cancer - Meena, Jitendra K; Wang, Jarey H; Neill, Nicholas J; Keough, Dianne; Putluri, Nagireddy; Katsonis, Panagiotis; Koire, Amanda M; Lee, Hyemin; Bowling, Elizabeth A; Tyagi, Siddhartha; Orellana, Mayra; Dominguez-Vidaña, Rocio; et al. (Cancer discovery, 2024)
Upregulation of MYC is a hallmark of cancer, wherein MYC drives oncogenic gene expression and elevates total RNA synthesis across cancer cell transcriptomes. Although this transcriptional anabolism fuels cancer growth and survival, the consequences and metabolic stresses induced by excess cellular RNA are poorly understood. Herein, we discover that RNA degradation and downstream ribonucleotide catabolism is a novel mechanism of MYC-induced cancer cell death. Combining genetics and metabolomics, we find that MYC increases RNA decay through the cytoplasmic exosome, resulting in the accumulation of cytotoxic RNA catabolites and reactive oxygen species. Notably, tumor-derived exosome mutations abrogate MYC-induced cell death, suggesting excess RNA decay may be toxic to human cancers. In agreement, purine salvage acts as a compensatory pathway that mitigates MYC-induced ribonucleotide catabolism, and inhibitors of purine salvage impair MYC+ tumor progression. Together, these data suggest that MYC-induced RNA decay is an oncogenic stress that can be exploited therapeutically. Significance: MYC is the most common oncogenic driver of poor-prognosis cancers but has been recalcitrant to therapeutic inhibition. We discovered a new vulnerability in MYC+ cancer where MYC induces cell death through excess RNA decay. Therapeutics that exacerbate downstream ribonucleotide catabolism provide a therapeutically tractable approach to TNBC (Triple-negative Breast Cancer) and other MYC-driven cancers.
Keywords: protoonkogenní proteiny c-myc; Gene Expression Regulation, Neoplastic; Cell Line, Tumor; regulace genové exprese u nádorů; stabilita RNA; nádory prsu; Animals; lidé; ženské pohlaví; Breast Neoplasms; ribonukleotidy; Humans; zvířata; RNA Stability; myši; Proto-Oncogene Proteins c-myc; nádorové buněčné linie; Mice; Female; Ribonucleotides